GREEN MARKETING STRATEGY, GREEN SUPPLY CHAIN MANAGEMENT, ON BUSINESS PERFORMANCE: GREEN INNOVATION AS MEDIATION - Rahmatullah, Arwin; Sutiono, Heru; Kusmantini, Titik (Faculty of Economic and Business, University of Pasundan, 2024)
This study aims to determine the role of green marketing strategy, green supply chain management on business performance with green innovation as a mediating variable in the creative economy in Yogyakarta. This research uses descriptive quantitative. The sample in this study were 60 SMEs. The sampling technique using purposive sampling. The data analysis method used in research is a Structural Equation Model (SEM) with Partial Least Square (PLS) 4.0. The results of this study The results of this study are green marketing strategy and green supply chain management affect business performance business performance. Green marketing strategy and green supply chain management affect green innovation. Green innovation affects business performance. Green innovation does not mediate the relationship of green marketing strategy to business performance. However, green innovation mediates the relationship between green supply chain management to business performance.